"They don't really take my bleeds seriously": Barriers to care for women with inherited bleeding disorders. (18th April 2021) - Arya, Sumedha; Wilton, Pamela; Page, David; Boma‐Fischer, Laurence; Floros, Georgina; Winikoff, Rochelle; Teitel, Jerome; Dainty, Katie; Sholzberg, Michelle
Abstract: Introduction: Women with inherited bleeding disorders experience excessive bleeding that may impair their quality of life, making early diagnosis and treatment critical. However, the experiences of these women regarding access to care has been minimally described. The primary objective of this study was to evaluate and describe barriers to care for women with bleeding disorders. This study was a continuation of our previous work describing the lived experiences of these women. Methods: We undertook a qualitative descriptive study. Inclusion criteria for study enrollment were the following: age ≥18 years, English‐speaking, and confirmed diagnosis of an inherited bleeding disorder. Women were recruited across Canada by treating health‐care providers and members of the Canadian Hemophilia Society. Telephone interviews were conducted using a semi‐structured interview style, transcribed verbatim, and analyzed using descriptive thematic analysis. Results: A total of 15 participants were interviewed. Median age was 31 years (range 24–70 years). Four primary themes surrounding barriers to care emerged: (1) lack of health‐care provider awareness of bleeding disorders, (2) health‐care provider dismissal of symptoms, (3) limited access to specialized care and treatment plans, and (4) need for self‐education and advocacy. Discussion: We found that women with inherited bleeding disorders experience tension with the health‐care system, feeling unheard and poorly understood. Based on our findings, we identified key knowledge and care gaps that could be addressed with awareness and educational initiatives: patient education on vaginal blood loss, updated medical curricula, clear referral guidelines, and telehealth initiatives for patients residing far from hemophilia treatment centers.